Letter from J O Barry-Walsh to Miss M O'Dullaghan - Barry-Walsh, J. O.; Anti-Partition League, APL (1939)
Typescript letter dated 3 June 1939,from the Organising Secretary of the Anti-Partition of Ireland League, arranging a meeting.